Using Technology Acceptance Model (TAM)Model to Assess the Lecturers’ Behavioral Intention to Use E- Learning System in University of Babylon - Hasan abboodi, Chasib; Nahi Abid, Rahman; Haider Mahmood, Nawrs (International Journal of Engineering and Technology, 2018)
E-learning becomes the advanced technology used to improve the learning process with professional tools. University of Babylon (UoB) has begun to adopt e- learning tools to improve its education quality. Lecturers acceptance of e-learning system is critical issue should be measured along time of development of e-learning system in order to get high effectiveness in learning process.Â The technology acceptance model (TAM) used in this study to explain lecturers' acceptance of e-learning system in UoB. the present paper consolidated the perceived Usefulness (PU), perceived ease of use (PEOU), perceived playfulness, facilitating conditions and IT knowledge as independent variables. Data gathered by distributed questionnaire. The number of respondents was fifty-nine. The findings demonstrated that PEOU, PU, perceived playfulness and IT knowledge are fundamentally affected the attitude of UoB lecturers. These were trailed by disposition to utilize E-learning and its encouraging condition impact user behavior.Â Â